Performance of native chicken given free choice feed - I.P Kompiang; Supriyati .; M.H Togatorop; S.N Jarmani (Indonesian Center for Animal Research and Development (ICARD), 2001)
An experiment was conducted to study the effect of free choice feeding on the performance of native chicken and to determine its protein and energy requirements for growth. Eight hundreds and seventy 2-weeks old native chicken were used, and divided into three treatment groups, with 5 replicates: (I) Complete feed (II) Choice feed A (two levels of protein, similar in energy content) and (III) Choice feed B (energy and protein sources). Feed and water were given ad libitum during the 10 weeks trial. Feed intake (protein and energy) and body weight were recorded biweekly. Body weight gain (BWG) of treatment I was 852 + 33 grams/head, similar to treatment II, 858 + 28 grams/head, and both significantly (P<0.05) better than treatment III (800 + 42 grams/head). Energy consumption and its energy efficiency ratio (EER) value were similar for all treatments, 9226 + 149; 9203 + 739, and 8706 + 383 kcal/head and 10.84 + 0.34, 10.75 + 1.03, and 10.89 + 0.27 kcal/gram for treatment I, II and III, respectively. There was a significant (P<0.05) difference between treatment on protein intake, 556 + 8, 506 + 15, and 454 + 25 grams/head for treatment I, II, and III, respectively. Protein energy ratio (PER) value of treatment III (0.57 ± 0.02) was similar to treatment II (0.57 ± 0.02) and both were significantly better (P<0.05) than treatment I (0.65 ± 0.02). It was concluded that the native chicken, given a correct choice of feed, has an ability to determine its energy and protein requirements. During the growth periods, 2-12 weeks old, the bird require feed with 16% protein and 2900 kcal metabolized energy/kg. Key word: Native chicken, feeding system, free choice